Expression of FoxP3 in different forms of leprosy and reactions - Chalita Patricia Lima; Elisa M. Costa; Lucas F. Sampaio
ABSTRACT Although regulatory T cells (Treg) are important in the immune regulation of various pathological processes, the role of these cells in the immunology of leprosy still needs to be better evaluated. The objective of this work is to quantify the FoxP3, the main marker of Treg cells, in the different forms of leprosy, with and without leprosy reaction. Expression of Treg cells was investigated using the enzyme-linked immunosorbent assay (ELISA) method to measure the FoxP3 marker in unstimulated plasma as well as in the peripheral blood mononuclear cells (PBMC) supernatant after incubation with M. leprae sonicated antigen (MLSA) for 72 hours. After stimulation with MLSA, a strong increase in FoxP3 expression was observed in multibacillary leprosy (MB), type 1 leprosy reaction (T1R) and type 2 leprosy reaction (T2R) patients. However, the group that presented the highest expression of FoxP3 was T1R, about six times more than that of healthy individuals and twice as many as T2R patients. Thus, this study suggests that Treg plays an important role in the etiopathogenesis of leprosy reactions, regulating the exacerbated acute inflammatory process, avoiding severe and incapacitating lesions. This study also demonstrates that ELISA, a simple and affordable technology, can be used in routine measurement of the FoxP3 marker.